Acute Kidney Injury in Patients Receiving Anti-Tuberculosis Treatment - Mehmood, Madiha; Anees, Muhammad (Pakistan Journal of Kidney Diseases, 2025)
Although life-saving, anti-tuberculosis therapy (ATT) carries the risk of acute kidney injury (AKI), potentially complicating its management. Methods: 102 subjects starting on ATT were followed for 2 months. Presence of AKI was documented with monitoring of kidney functions. Results: AKI was observed among 14.7% patients, predominantly affecting middle-aged males. Conclusion: Early recognition of AKI by monitoring for kidney function is crucial for reducing the risk of long-term sequelae of kidney failure among patients taking ATT.